The Effects of FDI on Skilled-unskilled Wage Gap in Thailand - HengLi (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The present study explores the effects of FDI on skilled-unskilled wage gap in Thailandusing the panel data from2008 to2017,based on prosperousstatusofFDI and income disparity problems of skilled and unskilled labor in Thailand. Due to wage gap is not a data value, this thesis employs 3 measurement methods to obtain the skilled-unskilled wage gap, that is the difference of income distribution deciles, the difference of average wage in skilled and unskilled, the ratio of skilled wage to unskilled wage. Panel Auto-Regressive Distributed Lag (Panel ARDL) is employed in this study. The pool Mean Group estimation (PMG) and Mean Group estimation (MG) are employed to estimate the long-run and short-run relationship, Hausman test is employed to choose which is the better estimator between PMG and MG. The results shows PMG is the best estimator based on the Hausman test. The evidence shows that FDI decreases the skilled-unskilled wage gap in long run. In the short run, there are different effects of different FDI sectors on skilled-unskilled wage gap.